The Lyrical and the Epic Studies of Modern Chinese Literature - Prüšek, Jaroslav (Indiana University Press, 1980)
With this volume, Prusek's enlightening essays on modern Chinese writings are available for the first time in book form. Prusek traces two traditions in Chinese literature-the lyrical/subjective strain of the literati and the epic/objective tradition of folk literature-and, through their interaction, demonstrates important relationships between traditional and modern Chinese literature. He further explores "correspondences" to both realistic and lyrical trends in European literature. Included in this collection are "Subjectivism and Individualism in Modern Chinese Literature,'' "Introduction to Studies in Modern Chinese Literature," "A Confrontation of Traditional Oriental Literature with Modern European Literature in the Context of the Chinese Literary Revolution," "Reality and Art in Chinese Literature," "Lu Hsün's 'Huai chiu': A Pre- cursor of Modern Chinese Literature," "The Changing Role of the Narrator in Chinese Novels at the Beginning of the Twentieth Century." "Mao Tun and Yü Ta-fu," and 'Yeh Shen-t'ao and Anton Chekov." A fascinating exchange of views between Pn'isek and another eminent scholar, C. T. Hsia, is presented in a final essay and in an appendix. Their differing methodologies, approaches, and standards of literary judgment provide the student of modern Chinese literature with some rewarding insights about the analysis of literary texts.